(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Security is a big issue for all networks in todayâ€™s enterprise environment. Many methods have been developed to secure the network infrastructure and communication over the Internet, among them the use of firewalls, encryption, and virtual private networks. Intrusion detection is a relatively new addition to such techniques. IDSes protect a system from attack, misuse, and compromise. It can also monitor network activity.Network traffic monitoring and measurement is increasingly regarded as an essential function for understanding and improving the performance and security of our cyber infrastructure Â Keywords: IDS, NTM, Pattern Matching, IMAP